Improving Class Interaction Using Hand-Made Wordless Picture Series for Preschoolers during Storytelling - Yustina Laurentius Sri Mulatsih; Muhammad Hanif; Suharno Suharno; Sri Anitah (Journal of Educational Science and Technology (EST), 2018)
Early childhood is a critical period for language development. Children need more language interactions with caregivers, for optimal its development. Narrative skill become the most power full point to language development. Promoting narrative skill for preschooler was challenging goals for kindergarten teachers. Prior research shows that storytelling promotes preschoolers’ language production and interaction. However, little is known about the potential role of wordless picture series books. Comparing to books with text, wordless picture books can foster more spontaneous language production and teachers’ feedback. In this study aims to find out the different level of class interactions of twenty preschoolers to their teachers using a wordless picture series book and a story book with text. The wordless picture series books were hand-made by teachers. We found that in the wordless picture series book condition teachers showed higher levels of instructional support. The result revealed a significant improvement of teachers’ quality of feedback during storytelling instruction. It was proofing that wordless picture series books may boost classroom interaction and finally support language development of preschool students.